'Hit your man where you can': Taxation strategies in the face of resistance at the British Cape Colony, c.1820 to 1910. Issue 3 (1st September 2020) - Gwaindepi, Abel; Siebrits, Krige
ABSTRACT: The topic of this article is the development of the tax system of the Cape Colony from 1820 to 1910. This period was crucial for the introduction and diffusion of modern taxes, and the Cape constitutes an important case as the prime settler-colony in Africa. The article uses a new tax dataset and evidence from official documents to trace and explain the Colony's growing revenue problems during this period. It shows that few changes were made to the tax system from the annexation of diamond fields in 1877 until the end of the South African War in 1902 and that the public coffers mainly benefitted indirectly from the Colony's increased prosperity via railway earnings. This, it is argued, largely reflected the success of efforts by the mining industry to block the introduction of new taxes. The article emphasizes the unusual form of this resistance: instead of undertaking conventional lobbying activities, industry representatives obtained positions of policymaking authority in the Cape Colony's then still immature system of democratic institutions. Hence, it draws on the experience of the Cape to show that immature democratic institutions can hamper fiscal capacity-building.